Efeito de parâmetros de redução de óxido de grafeno sobre a estruturação de aerogéis: um estudo por espectroscopias vibracionais - Duarte, Camila Miranda Fonseca (2025)
The increasing need for high-performance material solutions has found backing in the qualities of graphene and its derivatives. Its properties are closely linked to manufacturing processes due to its highly changeable structure. Understanding the sensitivity of graphene necessitates employing advanced characterization techniques to examine its structure and any potential alterations. This study investigated the impact of synthesis parameters on the reduction of graphene oxide (GO) by ascorbic acid, considering the characteristics of the GO precursor, the concentration and sonication time of the suspension, the reagent proportions, and the dispersion method of the reducing agent. GO was synthesized using the Hummers and mechanosynthesis methods, and characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy with Attenuated Total Reflection (FTIR-ATR), and Raman Spectroscopy, as were the aerogels. The results indicated that GO obtained via the Hummers method is more suitable for aerogel formation, due to the oxygenated groups at the edges and the moderate defect density. The aerogels, in turn, showed sensitivity to all the parameters analyzed, which influenced the structural organization and network stability, as studied through Raman spectral bands.